Pengaruh Desain Kemasan dan Perceived Quality terhadap Brand Loyalty: Studi Kasus Konsumen Bakerman di DKI Jakarta - Hendi Thamrin (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This study highlights the role of packaging design in attracting consumers and building brand loyalty in a competitive market. As a growing bakery brand in DKI Jakarta, Bakerman faces challenges in maintaining customer loyalty amid intense competition. Packaging design not only serves as product protection but also as a communication tool that shapes consumer perceptions of product quality and value. This study aims to analyze how packaging design elements, such as color, typography, and materials, influence Bakerman’s brand loyalty. Using a quantitative approach through surveys, data is collected from consumers in DKI Jakarta and analyzed using linear regression to understand the relationship between packaging design and brand loyalty. The findings are expected to contribute to the field of visual communication design and consumer behavior. Practically, this research provides strategic recommendations for Bakerman to optimize packaging design in strengthening customer loyalty and market competitiveness.